VULNERABILITIES AND COUNSELING IN HUMAN IMMUNODEFICIENCY VIRUS INFECTION (CIPEEX, 2022)
INTRODUCTION: EVEN AFTER 30 YEARS OF THE DISCOVERY OF ACQUIRED IMMUNODEFICIENCY SYNDROME, WE ARE CONFRONTED WITH PREJUDICED BEHAVIORS OF SOCIETY, PROFESSIONALS AND EVEN THOSE WITH THE HUMAN IMMUNODEFICIENCY VIRUS (HIV), WHICH INTERFERE WITH ADHERENCE TO ANTIRETROVIRAL TREATMENT (ART) AND MAKE IT DIFFICULT TO COPE WITH CONTRIBUTING TO THE PERPETUATION OF VIRUS TRANSMISSION. OBJECTIVES: TO INVESTIGATE, IN THE SCIENTIFIC LITERATURE, THE VULNERABILITIES AND COPING STRATEGIES ASSOCIATED WITH HIV STATUS. METHOD: THIS IS AN INTEGRATIVE LITERATURE REVIEW BASED ON EVIDENCE-BASED PRACTICE. DATA COLLECTION TOOK PLACE IN THE VIRTUAL HEALTH LIBRARY, THE SCIELO LIBRARY AND THE LILACS DATABASE. DESCRIPTORS WERE USED USING THE DECS: COPING, SOCIAL STIGMA, HIV, SOCIAL VULNERABILITY, SOCIAL SUPPORT, QUALITY OF LIFE AND SOCIAL PERCEPTION. THE CRITERIA FOR INCLUSION WERE ARTICLES IN PORTUGUESE, IN THE TIME CUT FROM 1996 TO 2018 AND WERE AVAILABLE IN FULL AND ONLINE. THE THEMATIC CATEGORIZATION OF ARTICLES WAS CARRIED OUT ACCORDING TO SOCIAL, INDIVIDUAL AND PROGRAMMATIC VULNERABILITY. RESULTS: AFTER APPLYING THE INCLUSION CRITERIA AND CONSIDERING THE PURPOSE OF THE STUDY, 13 ARTICLES WERE SELECTED. ALL PRODUCED IN PUBLIC INSTITUTIONS, BETWEEN THE YEARS 2004 TO 2017 IN THE SOUTHEASTERN AND NORTHEASTERN REGIONS OF BRAZIL. NINE WERE QUALITATIVE, THREE QUANTITATIVE AND A MIXED STUDY. REGARDING SOCIAL VULNERABILITY, THE AUTHORS HIGHLIGHTED THE SOCIAL STIGMA THAT THE HIV PATIENT FACES AND THIS INTERFERES WITH WORK, FRIENDSHIP AND ADHERENCE TO TREATMENT. REGARDING INDIVIDUAL VULNERABILITY, THE ARTICLES PROVIDE DATA ON THE GREATER DIFFICULTY OF COPING WITH HIV STATUS BY WOMEN, BLACKS AND MEN WHO HAVE SEX WITH MEN DUE TO THE PREJUDICE, MISOGYNY AND HOMOPHOBIA THEY FACE. IN PROGRAMMATIC VULNERABILITY THE TEXTS BRING PREJUDICE, A LACK OF OPENNESS TO TALK ABOUT SEXUALITY AND THE CONCEPTIONS, OFTEN BASED ON COMMON SENSE, THAT HEALTH PROFESSIONALS INSIST ON USING AT THE MOMENT OF PROVIDING CARE, IN ADDITION TO DOUBLE STIGMA AGAINST THE BEARER OF BLACK HIV. SUCH COPING STRATEGIES INCLUDED SELF-ACCEPTANCE OF THE NEW CONDITION, PARTICIPATION IN HIV POSITIVE GROUPS, SUPPORT FROM FRIENDS AND FAMILY, AND PURSUIT OF SPIRITUALITY-ORIENTED PRACTICES. FINAL CONSIDERATIONS: THERE ARE SEVERAL VULNERABILITIES ASSOCIATED WITH HIV STATUS, MANY OF WHICH EXIST EVEN BEFORE THE DIAGNOSIS OF THE INFECTION. THE STIGMA THAT PERMEATES SEROPOSITIVITY ARISES FROM DISCRIMINATION AND STIGMA THAT NEGATIVELY AFFECT THE PURSUIT OF POST-DIAGNOSIS. THE COPING STRATEGIES VARY FROM PERSON TO PERSON, WITH THE SUBJECTS' TIME AND EMOTIONS, EVEN INTERFERING WITH ART ADHERENCE. HEALTH PROFESSIONALS ARE KEY IN IDENTIFYING NEEDS AND ASSISTING HIV CARRIERS BY PROMOTING PERSEVERANCE IN TREATMENT, PROMOTING QUALITY OF LIFE AND DIGNITY.
Keywords: Social stigma. HIV. Social vulnerability